A new perspective to develop regiorandom polymer acceptors with high active layer ductility, excellent device stability, and high efficiency approaching 17%. Issue 2 (26th September 2022) - Fan, Qunping; Ma, Ruijie; Su, Wenyan; Zhu, Qinglian; Luo, Zhenghui; Chen, Kai; Tang, Yabing; Lin, Francis R.; Li, Yuxiang; Yan, He; Yang, Chuluo; Jen, Alex K.‐Y.; et al.
Abstract: The recently reported efficient polymerized small‐molecule acceptors (PSMAs) usually adopt a regioregular backbone by polymerizing small‐molecule acceptors precursors with a low‐reactivity 5‐brominated 3‐(dicyanomethylidene)indan‐1‐one (IC) end group or its derivatives, leading to low molecular weight, and thus reduce active layer mechanical properties. Herein, a series of newly designed chlorinated PSMAs originating from isomeric IC end groups are developed by adjusting chlorinated positions and copolymerized sites on end groups to achieve high molecular weight, favorable intermolecular interaction, and improved physicochemical properties. Compared with regioregular PY2Se‐Cl‐ o and PY2Se‐Cl‐ m, regiorandom PY2Se‐Cl‐ ran has a similar absorption profile, moderate lowest unoccupied molecular orbital level, and favorable intermolecular packing and crystallization properties. Moreover, the binary PM6:PY2Se‐Cl‐ ran blend achieves better ductility with a crack‐onset strain of 17.5% and improved power conversion efficiency (PCE) of 16.23% in all‐polymer solar cells (all‐PSCs) due to the higher molecular weight of PY2Se‐Cl‐ ran and optimized blend morphology, while the ternary PM6:J71:PY2Se‐Cl‐ ran blend offers an impressive PCE approaching 17% and excellent device stability, which are all crucial for potential practical applications of all‐PSCs in wearable electronics. To date, the efficiency of 16.86% is the highest value reported for the regiorandom PSMAs‐based all‐PSCs and is also one of the best values reported for the all‐PSCs. Our work provides a new perspective to develop efficient all‐PSCs, with all high active layer ductility, impressive PCE, and excellent device stability, towards practical applications. Abstract : A novel regiorandom chlorinated polymer acceptor PY2Se‐Cl‐ ran was developed. The binary PM6:PY2Se‐Cl‐ ran blend achieved a high efficiency of 16.23% in all‐polymer solar cells (PSCs) and an excellent ductility with a crack‐onset strain of 17.5%, while the ternary PM6:J71:PY2Se‐Cl‐ ran blend offered an impressive efficiency approaching 17% and excellent device stability, which are all crucial for the practical applications of all‐PSCs in wearable electronics.